2012
DOI: 10.1051/0004-6361/201219221
|View full text |Cite
|
Sign up to set email alerts
|

Ionization structure of hot components in symbiotic binaries during active phases

Abstract: Context. During active phases of symbiotic binaries, an optically thick medium in the form of a flared disk develops around their hot stars. During quiescent phases, this structure is not evident. Aims. We propose the formation of a flared neutral disk-like structure around the rotating white dwarf (WD) in symbiotic binaries. Methods. We applied the wind compression model and calculated the ionization boundaries in the compressed wind from the WD using the equation of photoionization equilibrium. Results. Duri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…4.4). Recently, Cariková & Skopal (2012) showed that the biconical ionization structure can be formed as a consequence of the enhanced massloss rate from the rotating WD during outbursts of symbiotic binaries. In their model, the opening of the H ii zone is related to the mass loss rate from the WD asṀ (ii) The neutral material within the H i zone, which has the form of a disk encompassing the hot WD, can persist within the ejecta for a much longer time than the duration of the fireball phase until it becomes totally ionized.…”
Section: 2 Of Skopal 2014b)mentioning
confidence: 99%
See 1 more Smart Citation
“…4.4). Recently, Cariková & Skopal (2012) showed that the biconical ionization structure can be formed as a consequence of the enhanced massloss rate from the rotating WD during outbursts of symbiotic binaries. In their model, the opening of the H ii zone is related to the mass loss rate from the WD asṀ (ii) The neutral material within the H i zone, which has the form of a disk encompassing the hot WD, can persist within the ejecta for a much longer time than the duration of the fireball phase until it becomes totally ionized.…”
Section: 2 Of Skopal 2014b)mentioning
confidence: 99%
“…This is probably a result of a decreasing mass-loss rate (see Sect. 4.4), which leads to a gradual ionization and hence flattening of the neutral disk (Cariková & Skopal 2012), which in turn leads to an enlargement of the H ii zone (see Sect. 4.3).…”
Section: Probing the Neutral Disk By The Raman-scatteringmentioning
confidence: 99%
“…References. 1) Cranmer & Owocki (1995); 2) Owocki et al (1996); 3) Cariková & Skopal (2012); 4) this paper. model S350 by Owocki et al (1994) as a representative Be star model: v rot = 350 km s −1 , M = 7.5 M , R pole = 4 R (at the critical velocity R max eq = 6 R ), and L = 2 310 L .…”
Section: Rapidly Rotating Be Starmentioning
confidence: 75%
“…Here we consider a typical WD in symbiotic binary with v rot = 300 km s −1 (Cariková & Skopal 2012) (5), respectively. This corresponds to the ratio R pole /R eq ∼ 0.996.…”
Section: Moderately Rotating Wdmentioning
confidence: 99%
See 1 more Smart Citation